2022
DOI: 10.1097/psy.0000000000001053
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Acceptance and Adherence to Noninvasive Ventilation in Chronic Obstructive Pulmonary Disease: A Randomized Controlled Trial

Abstract: ObjectivePeople with chronic obstructive pulmonary disease (COPD) may suffer from anxiety, depression, low quality of life, and cognitive deficits that could play a role in their clinical conditions. These situations could be worsened during the adaptation process to a new treatment such as noninvasive ventilation (NIV), which is often rejected or inappropriately used. The study aimed to analyze the impact of a brief psychological support intervention on adherence to NIV among patients with COPD.MethodsA two-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…For example, when implemented in respiratory medicine, and particularly in COPD, hypnosis has been mostly used as a form of “relaxation therapy” ( Cafarella et al, 2012 ; Tselebis et al, 2016 ). Certainly, hypnotic inductions often include relaxation exercises ( Batty et al, 2006 ), and of course, the implementation of hypnosis and other forms of guided mental imagery as a form of relaxation is beneficial in and of itself ( Hammond, 2010 ; Volpato et al, 2015 , 2022 ). However, as explained above, hypnotic effects depend primarily on the contents of suggestions ( Figure 1 ), which are fundamentally independent from hypnosis’ relaxation component ( Cardeña et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, when implemented in respiratory medicine, and particularly in COPD, hypnosis has been mostly used as a form of “relaxation therapy” ( Cafarella et al, 2012 ; Tselebis et al, 2016 ). Certainly, hypnotic inductions often include relaxation exercises ( Batty et al, 2006 ), and of course, the implementation of hypnosis and other forms of guided mental imagery as a form of relaxation is beneficial in and of itself ( Hammond, 2010 ; Volpato et al, 2015 , 2022 ). However, as explained above, hypnotic effects depend primarily on the contents of suggestions ( Figure 1 ), which are fundamentally independent from hypnosis’ relaxation component ( Cardeña et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 11 themes and 2 individual observations were identified by the reviewers for a total of 48 occurrences in the literature, whereas 11 themes and 7 observations were noted for a total of 95 observations. In the 33 studies analyzed, 26 (79%) showed an improvement in symptoms of depression [25,26,[28][29][30][31][32][33][35][36][37][40][41][42][43][44][46][47][48][49][50][51][52][54][55][56], while 19 (58%) showed an improvement in anxiety [26][27][28][29][30][31][32][33]36,[38][39][40][44][45][46][53][54][55][56]. Only 11/33 (33%) reported that at least one symptom was not statistically significant when compared with results from the control group, but the improvement was still noted [25]…”
Section: Results Of Interventions Compared With the Control Groupsmentioning
confidence: 99%
“…The following observations only occurred once in the literature: decrease in anger [26], decrease in decision conflict [30], decrease in decision regret [30], decreased digestive disturbance [26], decreased pain [26], increased medication adherence [41], and the intervention had no effect on self-efficacy [34]. [25,26,[28][29][30][31][32][33][35][36][37][40][41][42][43][44][46][47][48][49][50][51][52][54][55][56] 19 Reduced anxiety [26][27][28][29][30][31][32][33]36,[38][39][40][44][45][46][53]…”
Section: Results Of Interventions Compared With the Control Groupsmentioning
confidence: 99%
See 2 more Smart Citations